Produksi Program Acara Pro 2 Activity di Pro 2 RRI Semarang (Produser) - Dicky Aditya Wijaya; adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Radio is one of the mass media which has been around for a long time and has survived until the era of new media convergence. Radio midst of easy access to various new media to obtain information and entertainment. Radio Republik Indonesia (RRI) is the first radio station owned by the Government of Indonesia and was officially established on September 11, 1945. Radio Republik Indonesia (RRI) has 35 regional stations spread across various parts of the archipelago. RRI Semarang is one of the oldest radio stations in the city of Semarang. This radio has four channels and has a special channels aimed at youth segmentation. The channel is Pro 2 RRI. Pro 2 RRI has several programs, one of which is